MEKANISME DAN TORSI PENGEPRASAN TUNGGUL TEBU MENGGUNAKAN PISAU BAJAK PIRING YANG DIPUTAR - Lisyanto Lisyanto; E Namaken Sembiring; I Nengah Suastawa; Radite P A Setiawan; M H Bintoro Djoefrie (PERTETA, 2007)
ABSTRACT Cutting of sugar cane stubble is one of important activities in sugar cane agriculture system. Problems on labor and low quality of cutting have not been solved by manual cutting system. In addition, a kind of farm machinery, which work in rotating ways did not give a good result in doing the cutting of sugar cane stubble. Due to low quality of cutting and broken sugar cane stubble, it is not used any more. The problem of broken sugar cane stubble in mechanical cutting system should be solved by changing the system of cutting mechanism, prefering impact cutting to chips forming. The goal of the study is to analyze the mechanism of cutting on sugar cane stubble by using rotating disk plow and to develop a mathematical model in order to determine cutting force of sugar cane stubble. Method of analyzing on movement of node on edge is used to discribe a curve of edge movement. A mathematical model of cutting force was developed base on instant cutting area which was calculated using Simpson method, numerical integration system. Equations resulted from this study can be applied to simulate the movement of edge using input parameters, mainly: tilt angle, disk angle, angular velocity,linier velocity. Variety of PA 198 has the higher specific cutting resistance per area of cutting than the other varieties. The mathematical model developed can be used to determine the cutting force with a good result. Diterima: 12 Desember 2006, Disetujui: 12 Maret 2001